2021
DOI: 10.1001/jamanetworkopen.2021.24760
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Research Waste Among Randomized Clinical Trials in Gastric Cancer

Abstract: This cross-sectional study examines the characteristics and presence of research waste, defined as unpublished data, inadequate reporting, or avoidable design limitations, among randomized clinical trials in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Regarding the PRISMA 2009 statement, items two, five, eight, nine, 17, 22, and 24 need significant improvement. In recent years, the problem of reproducibility and the waste of resources in biomedical research have caused considerable concern in the scientific community ( 50 , 51 ). However, comprehensive and transparent reporting of the study design, study process, and final outcomes is key to avoiding these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the PRISMA 2009 statement, items two, five, eight, nine, 17, 22, and 24 need significant improvement. In recent years, the problem of reproducibility and the waste of resources in biomedical research have caused considerable concern in the scientific community ( 50 , 51 ). However, comprehensive and transparent reporting of the study design, study process, and final outcomes is key to avoiding these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have also validated our findings. In the research of characteristics among randomized controlled trials (RCTs) in gastric cancer, Lu et al noted that RCTs conducted in non-Asian regions (OR = 2.76; 95% CI: 1.03–7.35) or with multicenter designs (OR = 3.84; 95% CI: 1.58–9.38) or external funds (OR = 2.373; 95% CI: 1.05–5.38) were more likely to publish their outcomes [ 58 ]. A retrospective study of the literature by Canestaro et al also found that trials with multicenter designs (OR = 1.32; 95% CI: 1.16–1.45) were associated with study results publication [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research waste stems from research with little to no societal, educational or stakeholder benefit [ 4 ]. Poorly reported or unpublished results compound research waste, pose a risk to the care of future patients and present ethical concerns [ 5 , 12 ]. Although research waste is not a new problem, it was accelerated by the COVID-19 pandemic and was prevalent across trials, evidence synthesis and guidelines [ 2 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%